DESKRIPSI KEMAMPUAN SPASIAL SISWA SMP DITINJAU BERDASARKAN PERBEDAAN GENDER DAN KEMAMPUAN MATEMATIKA - Sucipto, Sucipto (Jurnal Ilmiah Soulmath : Jurnal Edukasi Pendidikan Matematika, 2017)
Spatial ability is closely related to the learning of geometry, such as helping students in solving geometry problems. This descriptive qualitative research aims to find out the profile of spatial ability of students in solving geometry problems in accordance with spatial ability indicator that has been prepared that is spatial perception, spatial visualization, mental rotation, spatial relation, and spatial orientation reviewed based on gender differences and students with math skills.The subjects of this study were 6 people consisting of 3 men with high, moderate, and low ability level and 3 women with high, moderate and low ability level. The determination of the subject is done by giving a math test. Instrument in the research is a test of math ability, spatial ability test, and interview guidance. Subjects were given spatial ability tests and interviews to obtain data and then analyzed the data collected. Based on the results of the analysis, it is found that high-ability male students and high-ability female students have relatively equal ability. Furthermore for the capable male students having all the spatial abilities. While female students are capable of not having the ability to spatially rotate the mind (mental rotation). Keywords: Spatial ability, gender, mathematics ability.